Development of a method of psychological impact on target audiences of gamers using modern information technologies - Yevseiev, Serhii; Milevskyi, Stanislav; Pribyliev, Yurii; Melenti, Yevhen; Nalivayko, Andriy; Bazarnyi, Serghii; Morozov, Oleksandr; Kazak, Iryna; Hrebeniuk, Alla; Ivashchenko, Oksana (Eastern-European Journal of Enterprise Technologies, 2025)
The object of research is the process of psychological influence on the target audience of gamers using information technologies. The problem of the lack of effective methods for assessing and correcting the psychophysiological state of players was solved. The proposed method of psychological influence on the target audience of gamers provides for the study of aspects of the use of interactive platforms in psychological operations and educational platforms based on gaming technologies. The features of the proposed method and the results obtained consist in taking into account the types of the target audience and influencing this audience by appropriate methods through the information content of a computer game. The method, which is based on the developed stochastic model, allows predicting the behavior of users of information technology – a computer game. The results of the study show that for the effective use of information technologies to increase the effect of psychological influence, it is necessary to adapt the information content to the peculiarities of perception of different types of gamers target audience. The proposed method provides in the dynamics of creating the prerequisites for the formation of a method of psychological influence on target audiences of gamers using modern information technologies. The developed method should be implemented in the following conditions for the use of information technologies: organizational (orientation on the desired audience); technical (requirements for computer equipment, software, etc.); social (introduction to game scenarios of the distribution of the game environment and game characters to different categories of social groups). The predicted psychological effects when using a computer game have been formed: emotional impact; increased motivation; formation of critical thinking; technical recommendations